2009
DOI: 10.1002/jrs.2378
|View full text |Cite
|
Sign up to set email alerts
|

Raman and IR spectra of the cation‐deficient Aurivillius layered crystal Bi2W2O9

Abstract: Raman and IR spectra of Bi 2 W 2 O 9 , the m = 2 member of the cation-deficient Aurivillius phase, have been measured. The obtained spectra are discussed using the factor group approach for the orthorhombic Pna2 1 (C 2v 9 ) space group. The results are compared with those obtained for Bi 2 WO 6 and some m = 2 members of Aurivillius family of bismuth layered ferroelectrics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 20 publications
3
16
0
Order By: Relevance
“…Hence, this emission profile (Figure 6b) implies that the local symmetry around Eu 3+ ion in Bi2W2O9 is without an inversion centre. This is in line with XRD studies which suggest substitution of rare earth atoms in the crystal structure since all atoms in Bi2W2O9 are reported to occupy C1 symmetry sites [39]. We also report luminescence properties of Bi2W2O9 powders doped with Pr 3+ ions for the first time, to the best of our knowledge.…”
Section: Optical Propertiessupporting
confidence: 90%
“…Hence, this emission profile (Figure 6b) implies that the local symmetry around Eu 3+ ion in Bi2W2O9 is without an inversion centre. This is in line with XRD studies which suggest substitution of rare earth atoms in the crystal structure since all atoms in Bi2W2O9 are reported to occupy C1 symmetry sites [39]. We also report luminescence properties of Bi2W2O9 powders doped with Pr 3+ ions for the first time, to the best of our knowledge.…”
Section: Optical Propertiessupporting
confidence: 90%
“…The short (W_O) bonds are characterised with absorption peaks in the range of 920-1007 cm − 1 [49,50]. Mazcka et al have reported IR and Raman spectra of layered Aurivilius type compound Bi 2 W 2 O 9 [51]. IR spectrum of Bi 2 W 2 O 9 is characterised by band at 850 cm −1 assigned to the asymmetric stretching modes of WO 6 octahedra, and band at 936 cm − 1 attributed to the vibration of significantly shorter W-O bonds for some apical oxygen atoms [51].…”
Section: Structural Analysismentioning
confidence: 98%
“…Mazcka et al have reported IR and Raman spectra of layered Aurivilius type compound Bi 2 W 2 O 9 [51]. IR spectrum of Bi 2 W 2 O 9 is characterised by band at 850 cm −1 assigned to the asymmetric stretching modes of WO 6 octahedra, and band at 936 cm − 1 attributed to the vibration of significantly shorter W-O bonds for some apical oxygen atoms [51]. Raman spectrum of Bi 2 W 2 O 9 phase does not contain bands above 900 cm −1 [51].…”
Section: Structural Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Ali et al 210 provide insight into thermally induced solid‐state polymorphic transformation of sulfathiazole using simultaneous in situ Raman spectroscopy and DSC. McZka et al 211 have published a Raman and IR spectral analysis of the cation‐deficient Aurivillius layered crystal Bi 2 W 2 O 9 . Temperature‐dependent Raman spectra of the ferroelectric Bi 4− x Nd x Ti 3 O 12 ( x = 0, 0.5, 0.85) single crystals were recorded by Liang et al 212 from 100–800 K and discussed their features in terms of their structural properties.…”
Section: Solid‐state Studiesmentioning
confidence: 99%